2023
DOI: 10.1007/s00464-023-10140-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of indocyanine green near-infrared fluorescence bowel perfusion assessment in colorectal surgery

Abstract: Background Indocyanine green near-infrared fluorescence bowel perfusion assessment has shown its potential benefit in preventing anastomotic leakage. However, the surgeon's subjective visual interpretation of the fluorescence signal limits the validity and reproducibility of the technique. Therefore, this study aimed to identify objective quantified bowel perfusion patterns in patients undergoing colorectal surgery using a standardized imaging protocol. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Previous studies were conducted to establish and gather validity evidence for a method of quantifying fluorescence angiography [ 20 24 ]. This revealed that bowel perfusion quantification is a feasible method to differentiate between different perfusion patterns, highlighting the possibility of using standardized imaging protocols [ 21 ]. According to a recent consensus paper on ICG fluorescence angiography, we concur with the authors’ standpoint that additional investigation into quantitatively evaluating fluorescence is imperative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies were conducted to establish and gather validity evidence for a method of quantifying fluorescence angiography [ 20 24 ]. This revealed that bowel perfusion quantification is a feasible method to differentiate between different perfusion patterns, highlighting the possibility of using standardized imaging protocols [ 21 ]. According to a recent consensus paper on ICG fluorescence angiography, we concur with the authors’ standpoint that additional investigation into quantitatively evaluating fluorescence is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent consensus paper on ICG fluorescence angiography, we concur with the authors’ standpoint that additional investigation into quantitatively evaluating fluorescence is imperative. This will help to reduce the subjective variability associated with perfusion assessment [ 21 ], and make it easier to compare study outcomes with different dyes, and will improve the validity and reproducibility of such data in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the potential importance of evaluating blood flow during colorectal surgery to decrease complications [31]. Therefore, it is expected that perfusion assessment should become an essential surgical procedure for ensuring patient safety in colorectal surgery [32].…”
Section: Study Limitationsmentioning
confidence: 99%